Diagnosis Penyakit Dispepsia menggunakan Metode Dempster-Shafer - Nurul Syahrani; Relita Buaton; Husnul Khair (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Dyspepsia is a gastroduodenal disorder that is often characterized by symptoms such as epigastric pain, burning, bloating, and a feeling of fullness after eating. Treatment of dyspepsia often requires examination by a specialist doctor, which may not always be easily accessible due to distance, cost, or time constraints. Therefore, this study aims to diagnose dyspepsia using the Dempster-Shafer method to identify possible dyspeptic diseases such as GERD, gastritis, dyspepsia, and gastric ulcers based on 16 detected symptoms and 4 different treatments. to make it easier for patients to consult and get an initial diagnosis without having to see a specialist doctor directly. From this study, it is expected to help patients get information on the initial diagnosis of the patient.